Socio-economic status and rationale of mango cultivation based on some selected areas in Rajshahi district of Bangladesh (Research in Agriculture Livestock and Fisheries, 2019)
The study was conducted among 104 mango producer through primary data collection to assess the profitability in mango production, demographic and socio-economic condition of farmers in four villages of Northern region of Bangladesh. The study encompasses the comparison of cost and profit of other crop with mango cultivation. Most farmers depend on mango production because the climate is unfavorable for field crop production but very conducive for mango cultivation in Barind ecosystem. Problem Confrontation Index (PCI) was used to measure the problems of mango production. On the basis of PCI formula, out of the 16 problems, insects and diseases infestation was identified as the major problem with PCI 429 followed by dropping of fruits and flowers with PCI 409. Lack of better varieties/ Seedling/ grafts, modern technology and climate change was also three major problems with PCI 387, 193 and 276 respectively. Cost and return analysis of mango production revealed that 10 mango varieties are founds as profitable with the higher working investment and human labor development. Cultivator had to spend 106659 taka for one hectors of land or 120 mango trees and average profit was 299010. Average profit from mango cultivation (299010Tk/ha) was higher than Average profit from onion cultivation (260412Tk/ha).Most farmers (about 87%) practiced intercropping with mango. the cost incurred by Harvesting, Sorting and Grading of mango cultivation was more than other crops. Although respondents certified that Rajshahi district is profitable in respect of mango production further study should be taken place with other variables and characteristics.Res. Agric., Livest. Fish.6(1): 79-90, April 2019